2020
DOI: 10.1002/cam4.2964
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results of targeted prostate‐specific membrane antigen imaging in evaluating the efficacy of a novel hormone agent in metastatic castration‐resistant prostate cancer

Abstract: To investigate the feasibility and effectiveness of prostate‐specific membrane antigen (PSMA) imaging to make response assessment regarding novel hormone treatment and to predict the outcomes for metastatic castration‐resistant prostate cancer (mCRPC) patients. This retrospective study enrolled 68 mCRPC patients who had daily received a novel hormone agent named abiraterone. Tc‐99m PSMA single‐photon emission computed tomography (SPECT/CT) was performed at the baseline (SPECT/CT1) and after 3‐6 months of treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Liu et al reported a novel PSMA inhibitor, 6-hydrazinonicotinate-amino-caproic acid-lysine-urea-glutamate (HYNIC-ALUG), which was labeled with 99m Tc [45]. Preliminary clinical results show that this probe can be used to guide surgical procedures to remove more metastatic lymph nodes, and it can be of great value for response assessment and prediction of the effectiveness of treatment in metastatic castration resistance prostate cancer (mCRPC) patients after long-term abiraterone treatment.…”
Section: Prostate-specific Membrane Antigen Targeting Radiotracersmentioning
confidence: 99%
“…Liu et al reported a novel PSMA inhibitor, 6-hydrazinonicotinate-amino-caproic acid-lysine-urea-glutamate (HYNIC-ALUG), which was labeled with 99m Tc [45]. Preliminary clinical results show that this probe can be used to guide surgical procedures to remove more metastatic lymph nodes, and it can be of great value for response assessment and prediction of the effectiveness of treatment in metastatic castration resistance prostate cancer (mCRPC) patients after long-term abiraterone treatment.…”
Section: Prostate-specific Membrane Antigen Targeting Radiotracersmentioning
confidence: 99%